2021
DOI: 10.21037/tcr-21-905
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of oncolytic viruses in the treatment of intermediate to advanced solid tumors: a systematic review and meta-analysis

Abstract: Background: Cancer treatment remains one of the most formidable challenges worldwide. Some novel treatment strategies, including molecularly targeted therapy, gene therapy, and cellular immunotherapy, have also been investigated to improve therapeutic effects for cancer patients and have demonstrated unexpected positive effects. This systematic review and meta-analysis evaluated the efficacy and safety of oncolytic virus (OV) monotherapy or combination therapy for intermediate to advanced solid tumors. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Moreover, systematic reviews and meta-analyses evaluated the efficacy and safety of OV in lung cancer and showed that the objective response rate was significantly higher in patients receiving oncolytic adenovirus H101 monotherapy or combination with chemotherapy than in patients only receiving chemotherapy. 159 There still is a long way to go before the use of optimized OVs will be sophisticated enough to become a standard part of a likely combined (immuno)therapy against lung cancer. For this, the pitfall of systemic OV application must be overcome.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, systematic reviews and meta-analyses evaluated the efficacy and safety of OV in lung cancer and showed that the objective response rate was significantly higher in patients receiving oncolytic adenovirus H101 monotherapy or combination with chemotherapy than in patients only receiving chemotherapy. 159 There still is a long way to go before the use of optimized OVs will be sophisticated enough to become a standard part of a likely combined (immuno)therapy against lung cancer. For this, the pitfall of systemic OV application must be overcome.…”
Section: Introductionmentioning
confidence: 99%
“…These viruses, which have been studied in many research settings, are known to have minimal human toxicity and to destroy tumoral cells specifically and they have a wide spectrum of anticancer activity. In a systematic review and meta-analysis, the authors studied 4000 patients treated for different cancers with oncolytic viruses (OVs) and concluded that this therapy was effective and well-tolerated as a treatment for advanced solid cancers and that it represents a promising therapeutic approach for solid cancers [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, changing the suppressed state of the tumor immune microenvironment has an essential role in clearing tumor cells. Oncolytic viruses can alter the cytokine milieu and enhance immune cell maturation and activation, restoring and increasing the body's function in tumor cell clearance (Raja et al, 2018;Galon and Bruni, 2019) (Figure 3).…”
Section: Regulation Of Anti-tumor Immunitymentioning
confidence: 99%